2017
DOI: 10.1002/adfm.201605985
|View full text |Cite
|
Sign up to set email alerts
|

A Drug‐Self‐Gated Mesoporous Antitumor Nanoplatform Based on pH‐Sensitive Dynamic Covalent Bond

Abstract: To achieve on‐demand drug release, mesoporous silica nanocarriers as antitumor platforms generally need to be gated with stimuli‐responsive capping agents. Herein, a “smart” mesoporous nanocarrier that is gated by the drug itself through a pH‐sensitive dynamic benzoic–imine covalent bond is demonstrated. The new system, which tactfully bypasses the use of auxiliary capping agents, could also exhibit desirable drug release at tumor tissues/cells and enhanced tumor inhibition. Moreover, a facile dynamic PEGylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(150 citation statements)
references
References 78 publications
3
147
0
Order By: Relevance
“…While at pH 6.5 (simulating tumor extracellular microenvironment), the DOX‐released percentage of the two PDA‐coated NPs reached about 37.4% and 38.9%, respectively. When the pH values decreased from 6.5 to 5.0 for simulating the environment of late endosomes/lysosomes, both of MSNs‐DOX@PDA and MSNs‐DOX@PDA‐TPGS exhibited a remarkably higher DOX release concentrations (51.6% and 47.7%, respectively). The conspicuous increase of DOX release of PDA‐modified NPs under acidic conditions suggested that upon decreasing the pH, PDA coating on the surfaces was partially removed, which unlocked the gate.…”
Section: Resultsmentioning
confidence: 99%
“…While at pH 6.5 (simulating tumor extracellular microenvironment), the DOX‐released percentage of the two PDA‐coated NPs reached about 37.4% and 38.9%, respectively. When the pH values decreased from 6.5 to 5.0 for simulating the environment of late endosomes/lysosomes, both of MSNs‐DOX@PDA and MSNs‐DOX@PDA‐TPGS exhibited a remarkably higher DOX release concentrations (51.6% and 47.7%, respectively). The conspicuous increase of DOX release of PDA‐modified NPs under acidic conditions suggested that upon decreasing the pH, PDA coating on the surfaces was partially removed, which unlocked the gate.…”
Section: Resultsmentioning
confidence: 99%
“…Outlets Capping with DOX : The outlets of mesoporous silica nanoparticles were capped with DOX using our previously published method with some modifications . 1 mg of DOX was predispersed in 1 mL of ethanol with the aid of sonication and then 2 mg of M‐R was added, followed by addition of sodium hydroxide aqueous solution (4.5 µL, 0.5 m ).…”
Section: Methodsmentioning
confidence: 99%
“…To prevent the leakage of siRNA, the pores of mesoporous silica should be blocked by a molecule gatekeeper. Our previous study reported a doxorubicin (DOX) molecularly gated strategy to control drug release by the formation of pH‐responsive benzoic–imine bonds on a benzaldehyde‐functionalized MSNs (M‐CHO) . This inspired us to load siRNA into a benzaldehyde‐functionalized mesoporous silica and then blocked it by DOX, finally achieving the codelivery of P‐gp siRNA and DOX.…”
Section: Introductionmentioning
confidence: 99%
“…[19,39] Here, we used a PTX prodrug as a GSHsensitive gatekeeper. [19,39] Here, we used a PTX prodrug as a GSHsensitive gatekeeper.…”
Section: Glutathione (Gsh)-dependent Drug Release and Nir-triggered Pmentioning
confidence: 99%